2014
DOI: 10.1016/j.micres.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of three sponge-associated Arthrobacter Antarctic strains, inhibiting the growth of Burkholderia cepacia complex bacteria by synthesizing volatile organic compounds

Abstract: In this work we analyzed the ability of three Arthrobacter strains (namely TB23, TB26 and CAL618), which were isolated from the Antarctic sponges Haliclonissa verrucosa and Lyssodendrix nobilis, to specifically inhibit the growth of a panel of 40 Burkholderia cepacia complex strains, representing a major cause of infections in patients that are affected by Cystic Fibrosis. The inhibitory activity was due to the synthesis of antimicrobial compounds, very likely volatile organic compounds (VOCs), and was partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Haliclonissaverrucosa Burton, 1932 with vouchers MNA 915, MNA 916, MNA 917, MNA 918; Anoxycalyx (Scolymastra) joubini (Topsent, 1916) with voucher MNA 928; Lissodendoryx (Ectyodoryx) nobilis (Ridley & Dendy, 1886) with voucher MNA 863) were previously published in other manuscripts (i.e. Fondi et al 2014; Orlandini et al 2014; Papaleo et al 2013; 2012; Mangano et al 2009; Romoli et al 2011) without an MNA catalogue number which have been assigned after the publication. In the collection is also present an uncommon sponge (i.e.…”
Section: Taxonomic Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Haliclonissaverrucosa Burton, 1932 with vouchers MNA 915, MNA 916, MNA 917, MNA 918; Anoxycalyx (Scolymastra) joubini (Topsent, 1916) with voucher MNA 928; Lissodendoryx (Ectyodoryx) nobilis (Ridley & Dendy, 1886) with voucher MNA 863) were previously published in other manuscripts (i.e. Fondi et al 2014; Orlandini et al 2014; Papaleo et al 2013; 2012; Mangano et al 2009; Romoli et al 2011) without an MNA catalogue number which have been assigned after the publication. In the collection is also present an uncommon sponge (i.e.…”
Section: Taxonomic Coveragementioning
confidence: 99%
“…In total, the dataset includes 144 different morphospecies, and a total of 807 specimens. Several studies were based on this dataset: Alvizu et al (in press); Bertolino et al 2009; Calcinai et al 2000; Cattaneo-Vietti et al 2000; Fondi et al 2014; Mangano et al 2009; Orlandini et al 2014; Papaleo et al 2012, 2013; Romoli et al 2011; Sarà 2002; Sarà et al 1992. The validity and synonyms of each species name were checked in WORMS (World Register of Marine Species; http://www.marinespecies.org; last check made on 2018-03-28).…”
Section: Taxonomic Coveragementioning
confidence: 99%
“…It has recently been demonstrated that bacteria are able to inhibit the growth of Burkholderia cepacia complex (Bcc) strains through the synthesis of MVOCs (Papaleo et al, 2012, 2013; Orlandini et al, 2014). Reported data show that two Pseudoalteromonas strains were able to completely inhibit the growth of most Bcc strains (Romoli et al, 2011).…”
Section: Overview Of Bioactive Bacterial Volatilesmentioning
confidence: 99%
“…Y81 from Tibetan Plateau (TP) lake, Arthrobacter sp. TB 26 from Antarctica marine sponge (52), Arthrobacter sp. FB24 from soil in Seymour, Indiana (53) and Arthrobacter sp.…”
Section: Resultsmentioning
confidence: 99%